Um estudo de caso sobre avaliação de uma API de sistema Web baseado em Microsserviços - Araújo, Samuel Gomes Bezerra (2021)
In recent times, the architectural pattern of microservices has established itself as a good alternative for Web systems. In this context, it is important to have a module that centralizes and controls access to other modules, such an element is usually called an API. An API is a set of programming code that is part of an interface and that allows the creation of different softwares, applications, programs and platforms in a way that makes life easier for developers. This work has as main objective to carry out an evaluation of an API of an interactive video system that uses the microservices architectural pattern. For this, a documentation of the current architecture of the system's object of analysis was elaborated and then static and dynamic evaluation of source code were carried out. From the study, it was possible to propose changes to the system that provide improvements in terms of safety and maintenance attributes.